Practical aspects of organizational culture assessment - E. M. Shironina (Вестник университета, 2020)
Organizational culture activates the ability to effectively solve management problems and plays a positive role in the development of the organization, provided, that managers are aware of its significance and have appropriate knowledge. The results of organizational culture study of one of the companies in the Perm territory using two methods: Organizational Culture Assessment Instrument (OCAI) and the method by S. I. Cordon, have been given in the article. Application of foreign and domestic methods gave comparable results: clan organizational culture according to OCAI correlates with the type of culture "Family", highlighted by S. I. Cordon, adhocratic culture - with the type of culture "Business". The results of organizational culture assessment of the organization under study and directions of possible managerial influences have been presented in the article.